A review of methods for estimating the contribution of glacial meltwater to total watershed discharge. (April 2014) - Frenierre, Jeff La; Mark, Bryan G.
Glaciers store water over a range of temporal scales with important implications for downstream human and natural systems. Assessment of the contribution of glacial meltwater runoff to total watershed discharge is an essential part of climate change risk assessment and sustainable water management in glacierized watersheds. Over the past decade, a range of techniques for quantifying the proportional contribution of glacial meltwater has been presented in the scientific literature. Here we examine five different methodological approaches: direct discharge measurement, glaciological approaches, hydrological balance equations, hydrochemical tracers, and hydrological modeling. After a brief summary of the role of glaciers in watershed hydrology, we evaluate each approach, with regard to their respective data requirements, assumptions, and associated uncertainties. Next, we discuss factors that researchers must consider in deciding upon a particular methodological approach, then conclude with a discussion of future research needs. We underscore the need for expanded meteorological, hydrological, and glaciological monitoring networks in glacierized watersheds worldwide, for more comprehensive assessment of uncertainty and for better integration of research with the specific needs of watershed stakeholders.